Factors influencing adoption of payments banks by Indian customers: extending UTAUT with perceived credibility. Issue 2 (21st March 2019) - Gupta, Kriti Priya; Manrai, Rishi; Goel, Utkarsh
Abstract : Purpose: The purpose of this paper is to investigate the factors influencing the behavioral intention to adopt payments banks services by Indian underbanked and unbanked population. Design/methodology/approach: The proposed model has assimilated factors from the Unified Theory of Acceptance and Use of Technology (UTAUT) along with perceived credibility. The factors of UTAUT include performance expectancy, effort expectancy, facilitation of conditions and social influence. Apart from testing the direct relationships of the model constructs with the behavioral intention to adopt payments banks services, the study has also explored mediating and moderating effects of certain constructs. The research model has been empirically tested using 660 responses from a field survey conducted in New Delhi – the capital city of India – by using the structured equation modeling (SEM) technique. The target respondents of the study are small businessmen and migrant laborers who are either underbanked or unbanked. Findings: The findings of the study reveal that the model is able to explain 67.5 per cent of the variance in behavioral intention. The results indicate that all the factors are direct determinants of behavioral intention. Perceived credibility is found to be the strongest influencer of behavioral intention. The findings also indicate that perceived credibility partially mediates the relationships between "social influence and behavioral intention" and "performance expectancy and behavioral intention." The relationship between performance expectancy and behavioral intention is also found to be moderated by facilitating conditions and effort expectancy. Research limitations/implications: As this study is based on a convenience sample of respondents of only one city of India, this could negatively reflect on the generalizability of results across other cities. Moreover, the study has only focused on the perceptions of small businessmen and migrant laborers. This raises concerns regarding the applicability of the results for other segments of the current population that have different demographic characteristics (e.g. occupation, income, education level and technology experience). Modifying the conceptual model presented in this research to include "experience" and "age" as moderators can also be worth considering in future. Although this study has extended the UTAUT to include perceived credibility, the results of the explanatory power of the model indicate that there is still room for improvement. Therefore, including other constructs, e.g. hedonic motivation, perceived risks and trialability, could be a fruitful path forward. Future studies may also examine the factors influencing the actual use behavior of payments banks, rather than just behavioral intention. Practical implications: The study looks forward to providing the payments banks service providers in India with suitable guidelines for effectively implementing and designing payments banks services. Specifically, the results of this study have provided clues for Indian payments banks service providers about the crucial role of perceived credibility in influencing the behavioral intention to adopt payments banks. Therefore, service providers have to initially be sure that payments banks are able to conduct financial transactions efficiently, securely and within less time, along with the availability of information required by customers to successfully use the services. Service providers should enhance customer confidence and trust by providing secure and reliable services. They should also emphasize on the positive safety measures of the payments banks during any marketing campaign rather than just creating brand awareness. Originality/value: The study represents a substantial contribution to the existing knowledge regarding mobile payment channels in particular and technology acceptance area in general. In fact, this study presents a worthwhile direction by examining payments banks services, which, so far, have not been well evaluated in the Indian context. To the best of the authors' knowledge, this is an early attempt toward a holistic and integrative approach to explain adoption of payments banks in India. Although prior studies have addressed mobile banking and mobile payment adoption, the strength of this research lies in combining the UTAUT constructs with perceived credibility. This is evidenced by the high explanatory power (67.5 per cent) of the research model adopted in this study.